Primary biliary cirrhosis: contribution of HLA class II allele DR8. - Gregory, W; Mehal, W; Dunn, A; Cavanagh, G; Chapman, R; Fleming, K; Daly, A; Idle, JR; James, O; Bassendine, M (1993)
Primary biliary cirrhosis is a chronic cholestatic disease of unknown aetiology which predominantly affects middle-aged women. It is thought to be autoimmune in nature, but unlike many autoimmune diseases no clear HLA association has been described. Several studies have suggested conflicting associations with HLA class II, although a DR8 association is most frequently described. To test the hypothesis that primary biliary cirrhosis is associated with a certain HLA class II locus we genotyped 130 patients with the disease from the north-east region of England and 363 local healthy controls. HLA-DRB1 and confirmatory DQA and DQB genotypes were determined by TaqI restriction fragment DNA length polymorphism analysis. In addition, a polymerase chain reaction technique (double ARMS) was used to investigate the DRB3 locus (DR52) in 98 primary biliary cirrhosis patients and 107 local controls. We found an increased frequency of HLA-DR8 (18.5% vs 9.2%, p < 0.005, relative risk of 2.0 [1.3-3.1]) in the primary biliary cirrhosis group. HLA-DR8-positive primary biliary cirrhosis patients had a higher serum bilirubin level (p = 0.03) than DR8-negative patients. There was no difference in the DR52 frequencies and no association with markers of disease severity. These results support earlier serological findings, although the association between primary biliary cirrhosis and DR8 is weaker than previously described. In addition, DR8-positivity may identify a clinical subgroup with a worse prognosis.